2005
DOI: 10.4103/0253-7613.16850
|View full text |Cite
|
Sign up to set email alerts
|

New uses for old drugs: Novel therapeutic options

Abstract: killer, was used to reduce the mortality rate among heart attack victims; the drug mitomycin, approved for the treatment of gastric and pancreatic cancers, has been found to be useful in the treatment of lung, bladder, breast and cervical cancers, as well as in certain forms of leukemia; trimethoprim, a drug approved to treat pneumonia, has been proved useful as an AIDS management. [4] Moreover, discovering new uses for a new drug that does not work out for its intended use may be another aspect of utilizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Drug discovery is an expensive and time-consuming process, and one solution is to find new uses for the existing drugs 27 . Because of the known pharmacokinetics and safety profiles, the old drugs could be approved by regulatory agencies for human use easily 28 .…”
mentioning
confidence: 99%
“…Drug discovery is an expensive and time-consuming process, and one solution is to find new uses for the existing drugs 27 . Because of the known pharmacokinetics and safety profiles, the old drugs could be approved by regulatory agencies for human use easily 28 .…”
mentioning
confidence: 99%
“…Even patients for whom documentation of previous exposure to fluoroquinolones is difficult have high rates of fluoroquinolones resistance, particularly among MDR-TB patients. A recent study from India showed that 15% of isolates from patients with susceptibility to first-line TB drugs were resistant to the fluoroquinolones, as well as almost 40% of isolates with MDR-TB [93]. These studies document the risk of resistance to the fluoroquinolones with current practice.…”
Section: Alternate Use Of Existing Agentsmentioning
confidence: 97%
“…Pharmacy practitioners should question potentially inappropriate medication orders, and published evidence to justify new medication uses should be shared with all members of the health-care team. 13 Beyond the aforementioned efficacy and safety concerns, the practice of using old medications in new ways may increase legal risk. While clinicians may be confident using medications for uses with little evidence, patients may be less willing to use drugs in novel ways.…”
Section: Disadvantages Of Using Old Drugsmentioning
confidence: 99%
“…Discoveries of other new uses may be made as a result of expanded knowledge regarding the pharmacologic properties of a medication, which can lead to identification of potential therapeutic targets. 13,14 Industry-based researchers may also use compound libraries to identify potential compounds of interest. Examples of these libraries include the Johns Hopkins Clinical Compound Library, the National Institute of Neurological Disorders and Stroke custom collection, the Prestwick Chemical Library, and the Sigma-Aldrich Library of Pharmacologically Active Compounds.…”
Section: Approaches To Finding New Usesmentioning
confidence: 99%